Quadriceps Tendon Rupture in an Emergency Department Patient with Left Knee Pain - Andrew G. Theophanous; Rebecca G. Theophanous (Diagnostics, 2026)
Point-of-care ultrasound (POCUS) is a dynamic imaging modality that can diagnose musculoskeletal and tendon injuries to facilitate appropriate orthopedic care and improve patient outcomes. This manuscript illustrates the value of dynamic POCUS to distinguish between complete and partial tendon injuries at the patient’s bedside, which is important for management and disposition planning in emergency department (ED) or clinic patients with acute trauma. In this case, a healthy 34-year-old male presented with acute left knee pain and swelling after a fall. He had a deformity superior to his patella and could not actively extend his left knee. Left knee X-ray was negative for fracture. POCUS demonstrated a disrupted left distal quadriceps tendon with anechoic fluid, tendon enlargement, and proximal tendon retraction. Importantly, a dynamic POCUS video cine loop revealed no contiguous tendon mobility with passive extension of the left knee (when movement is performed by the physician), confirming that this was a complete and not partial tendon tear. The patient was discharged in an extension knee brace. Outpatient magnetic resonance imaging confirmed the complete left quadriceps tendon rupture, and he underwent orthopedic surgery with good outcomes. Thus, early dynamic musculoskeletal POCUS confirmed a complete tendon injury, guiding expedited surgical treatment to prevent permanent damage and disability.